Nearshore mixing and nutrient delivery along the western Antarctic Peninsula - Corbett, D. Reide (David Reide), 1971-; Crenshaw, Jared; NULL, KIMBERLY; PETERSON, RICHARD N.; PETERSON, LEIGHA E.; LYONS, W. BERRY (My University, 2017)
The surface waters of the Southern Ocean play a key role in the global climate and carbon cycles by promoting growth of some of the world’s largest phytoplankton blooms. Several studies have emphasized the importance of glacial and sediment inputs of Fe that fuel the primary production of the Fe-limited Southern Ocean. Although the fertile surface waters along the shelf of the western Antarctic Peninsula (WAP) are influenced by large inputs of freshwater, this freshwater may take multiple pathways (e.g. calving, streams, groundwater discharge) with different degrees of water-rock interactions leading to variable Fe flux to coastal waters. During the summers of 2012–13 and 2013–14, seawater samples were collected along the WAP, near Anvers Island, to observe water column dynamics in nearshore and offshore waters. Tracers (223,224Ra, 222Rn, 18O, 2H) were used to evaluate the source and transport of water and nutrients in coastal fjords and across the shelf. Coastal waters are compared across two field seasons, with increased freshwater observed 2 -1 during2014.HorizontalmixingratesofwatermassesalongtheWAPrangedfrom110–3600m s .These mixing rates suggest a rapid transport mechanism for moving meltwater offshore.